Energy performance analysis of variable refrigerant flow system retrofit: a building consumption comparison study / M. A. Abdul Aziz ... [et al.] - Abdul Aziz, M. A.; Abd Razak, A.; Mohamad, M. F.; Jaafar, A. A. (Smart Manufacturing Research Institute (SMRI), 2025)
This study investigates the energy-saving potential of retrofitting an academic building at Universiti Teknologi MARA (UiTM) by replacing a conventional water-cooled chiller system with a Variable Refrigerant Flow (VRF) system. The research focuses on the College of Built Environment's academic building, which has a total area of 251.68 m², comprising 3,441.76 m² of conditioned space. Using Option C of the International Performance Measurement and Verification Protocol (IPMVP), the study compared pre-retrofit (2019) and post-retrofit (2023) energy consumption data. The analysis revealed that the VRF system implementation resulted in a 15.13% reduction in total building energy consumption, from 32,233 kWh to 27,356 kWh. With air conditioning accounting for 66% of the building's energy usage, the retrofit achieves a significant decrease in the ACMV system's energy consumption from 21,273.78 kWh to 16,396.78 kWh. The economic analysis, based on TNB Tariff C1 (Medium Voltage General Commercial), demonstrates monthly cost savings of RM 5,411, equivalent to an annual reduction of RM 64,935. These findings provide empirical evidence supporting the effectiveness of VRF systems in achieving substantial energy and cost savings of academic building applications within Malaysia's tropical climate.